The plastid genome of Deschampsia cespitosa (Poaceae) - Chiapella, Jorge Oscar; Barfuss, Michael; Xue, Zhi-Qing; Greimler, Josef (Molecules)
Plastid genome analysis of non-model organisms provides valuable information for basic research e.g., molecular evolutionary genomics, phylogeny and phylogeography. Deschampsia cespitosa is the most widespread species of the genus and it is a common grass that is found across Eurasia and North America. Scattered populations in regions of appropriate ecological conditions are also found in Australia, New Zealand and southern South America, where it is sympatric with D. antarctica. We analyzed the plastid genome of a sample of Deschampsia cespitosa of the Austrian Alps using high-throughput sequencing. The plastid (cp) genome shows the typical quadripartite structure with a length of 135,340 bp, comprising a large single-copy (LSC) region of 79,992 bp, a small single-copy (SSC) region of 12,572 bp and two inverted repeats (IR) regions of 21,388 bp each. It contains 115 genes,including 85 protein-coding genes, four ribosomal RNA genes and 30 transfer RNA genes. The GC content (%), number of repeats and microsatellites, RNA editing sites and codon usage were highly similar to those of D. antarctica. The results of this present study highlight the extremely conserved nature of the cp genome in this group, since the comparison involved individuals separated by about 13,000 km, from the Alps to Antarctica. Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Barfuss, Michael. Universidad de Viena. Instituto de Botanica; Austria Fil: Xue, Zhi-Qing. Universidad de Viena. Instituto de Botanica; Austria Fil: Greimler, Josef. Universidad de Viena. Instituto de Botanica; Austria